PENGARUH ETOS KERJA TERHADAP UPAH KARYAWAN DI TEMPAT PRAKTIK KETERAMPILAN USAHA TEBUIRENG JOMBANG PERSPEKTIF ETIKA BISNIS SYARI’AH - Achmad Fathoni Alfaris; Norma Fitria (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
In the context of the workplace, work ethic is a crucial factor in ensuring that employee performance is recognized fairly, professionally, and in accordance with the principles of Islamic ethics. This study is grounded in theoretical concepts concerning workers, work ethics, wage systems, and the principles of Islamic business ethics, which emphasize Islamic values such as honesty, justice, responsibility, and balance. Using an empirical juridical method and a conceptual approach, data were obtained through direct observation of work activities and the wage system at the Tebuireng Vocational Skills Training Center. The study examines the extent to which employee work ethics influence wage policy implementation and its alignment with Islamic business ethics by observing aspects such as discipline, responsibility, loyalty, and the form of compensation provided. The results indicate that work ethics have been well-implemented, as evidenced by the high commitment and performance of the employees. However, due to the strong pesantren (Islamic boarding school) culture, there is a reluctance among some employees to voice concerns about inadequate wages, resulting in only partial reflection of justice and transparency as outlined in Islamic business ethics. Therefore, improvements in the wage system are necessary to better align with Islamic values of justice. The findings of this research are expected to contribute to the development of ethical work practices and serve as a reference for pesantren-based business institutions in managing human resources in accordance with Islamic principles.